2018
DOI: 10.1088/2053-1583/aaaa8b
|View full text |Cite
|
Sign up to set email alerts
|

Exciton broadening and band renormalization due to Dexter-like intervalley coupling

Abstract: A remarkable property of atomically thin transition metal dichalcogenides (TMDs) is the possibility to selectively address single valleys by circularly polarized light. In the context of technological applications, it is very important to understand possible intervalley coupling mechanisms. Here, we show how the Dexter-like intervalley coupling mixes A and B states from opposite valleys leading to a significant broadening of the B1s exciton. The effect is much more pronounced in tungsten-based TMDs, where the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 41 publications
2
34
1
Order By: Relevance
“…where trueξ¯ represents the valley opposed to ξ , i.e., trueξ¯= = K′ for ξ = K. The small deviations from the band edges have been omitted in the Bloch functions since they are negligible compared with the distance between the corners of the hexagonal Brillouin zone. These interactions have been introduced as the k ‐space equivalent of the Dexter transfer . For large momentum transfer Δξ¯,ξ+bold-italicP on the order of the reciprocal lattice vector the Rytova–Keldysh potential is not valid anymore and the effective screening trueϵˆ must be adapted to density functional theory calculations …”
Section: Interband Polarizationmentioning
confidence: 99%
“…where trueξ¯ represents the valley opposed to ξ , i.e., trueξ¯= = K′ for ξ = K. The small deviations from the band edges have been omitted in the Bloch functions since they are negligible compared with the distance between the corners of the hexagonal Brillouin zone. These interactions have been introduced as the k ‐space equivalent of the Dexter transfer . For large momentum transfer Δξ¯,ξ+bold-italicP on the order of the reciprocal lattice vector the Rytova–Keldysh potential is not valid anymore and the effective screening trueϵˆ must be adapted to density functional theory calculations …”
Section: Interband Polarizationmentioning
confidence: 99%
“…In this Letter, we study the ultrafast intervalley transfer and relaxation dynamics including simultaneous intervalley exchange and phonon scattering and discuss their role for experimentally observed bleaching in transient pump-probe spectra: After optical excitation of the A transition, a significant bleaching at the B transition was observed. [18][19][20][21] Since the energy of the probed B exciton is hundreds of meV larger [9] compared to the A exciton this type of response comes as a surprise. In particular the helicity resolved data in WS 2 show that the bleaching of the B transition occurs not only in the unpumped valley but also within the pumped valley which, without considering further interactions, can only be attributed to an ultrafast spin flip of the electron [21] or to a mixture of A and B exciton states [22].…”
mentioning
confidence: 99%
“…In particular the helicity resolved data in WS 2 show that the bleaching of the B transition occurs not only in the unpumped valley but also within the pumped valley which, without considering further interactions, can only be attributed to an ultrafast spin flip of the electron [21] or to a mixture of A and B exciton states [22]. Interestingly, it was found that the bleaching of the B exciton in the unpumped valley rises faster compared to the pumped valley after optical excitation of the A transition [19][20][21].…”
mentioning
confidence: 99%
See 2 more Smart Citations